Safety and efficacy of upadacitinib in patients with active rheumatoid arthritis refractory to biologic disease-modifying anti-rheumatic drugs (SELECT-BEYOND): a double-blind, randomised controlled phase 3 trial. Issue 10139 (23rd June 2018) - Genovese, Mark C; Fleischmann, Roy; Combe, Bernard; Hall, Stephen; Rubbert-Roth, Andrea; Zhang, Ying; Zhou, Yijie; Mohamed, Mohamed-Eslam F; Meerwein, Sebastian; Pangan, Aileen L
Summary: Background: Phase 2 studies with upadacitinib, a selective Janus kinase 1 (JAK1) inhibitor, have shown safety and efficacy in the treatment of patients with active rheumatoid arthritis. We did this study to further assess the safety and efficacy of upadacitinib in patients with an inadequate response to biologic disease-modifying anti-rheumatic drugs (bDMARDs). Methods: We did this double-blind, randomised controlled phase 3 trial at 153 sites in 26 countries. Patients were aged 18 years or older, had active rheumatoid arthritis and previous inadequate response or intolerance to bDMARDs, and were receiving concomitant background conventional synthetic DMARDS (csDMARDs). We randomly assigned patients (2:2:1:1) by interactive response technology to receive once-daily oral extended-release upadacitinib 15 mg or 30 mg or placebo for 12 weeks, followed by upadacitinib 15 mg or 30 mg from week 12 onwards. The two separate primary endpoints were the proportions of patients achieving a 20% improvement in American College of Rheumatology criteria (ACR20) at week 12 and the proportion of patients achieving a 28-joint disease activity score using C-reactive protein (DAS28[CRP]) of 3·2 or less at week 12. Efficacy and safety analyses were done in the modified intention-to-treat population of all patients who received at least one dose of study drug. Data are presented up to week 24 of this ongoing study. The trial is registered withClinicalTrials.gov (NCT02706847 ). Findings: Between March 15, 2016, and Jan 10, 2017, 499 patients were randomly assigned (n=165 upadacitinib 15 mg; n=165 upadacitinib 30 mg; n=85 placebo then upadacitinib 15 mg; and n=84 placebo then upadacitinib 30 mg) and one patient was withdrawn from the 15 mg upadacitinib group before the start of study treatment. Mean disease duration was 13·2 years (SD 9·5); 235 (47%) of 498 patients had received one previous bDMARD, 137 (28%) had received two, and 125 (25%) had received at least three; 451 (91%) patients completed treatment up to week 12 and 419 (84%) patients completed treatment up to week 24. At week 12, ACR20 was achieved by 106 (65%; 95% CI 57–72) of 164 patients receiving upadacitinib 15 mg and 93 (56%; 49–64) of 165 patients receiving upadacitinib 30 mg compared with 48 (28%; 22–35) of 169 patients receiving placebo (p<0·0001 for each dose vs placebo). DAS28(CRP) of 3·2 or less was achieved by 71 (43%; 95% CI 36–51) of 164 patients receiving upadacitinib 15 mg and 70 (42%; 35–50) of 165 patients receiving upadacitinib 30 mg versus 24 (14%; 9–20) of 169 patients receiving placebo (p<0·0001 for each dose vs placebo). Up to week 12, overall numbers of patients with adverse events were similar for the placebo group (95 [56%] of 169) and the upadacitinib 15 mg group (91 [55%] of 164), but higher in the upadacitinib 30 mg group (111 [67%] of 165). At week 12, the most common adverse events occurring in at least 5% of patients in any treatment group were upper respiratory tract infection (13 [8%] of 169 in the placebo group; 13 [8%] of 164 in the upadacitinib 15 mg group; ten [6%] of 165 in the upadacitinib 30 mg group), nasopharyngitis (11 [7%]; seven [4%]; nine [5%]), urinary tract infection (ten [6%]; 15 [9%]; nine [5%]), and worsening of rheumatoid arthritis (ten [6%]; four [2%]; six [4%]). The number of patients with serious adverse events was higher in the upadacitinib 30 mg group (12 [7%]) than in the upadacitinib 15 mg group (eight [5%]); no serious adverse events were reported in patients receiving placebo. More patients in the upadacitinib 30 mg group had serious infections, herpes zoster, and adverse events leading to discontinuation than in the upadacitinib 15 mg and placebo groups. During the placebo-controlled phase of the study, one case of pulmonary embolism, three malignancies, one major adverse cardiovascular event, and one death were reported in patients receiving upadacitinib; none were reported in patients receiving placebo. Interpretation: Both doses of upadacitinib led to rapid and significant improvements compared with placebo over 12 weeks in patients with refractory rheumatoid arthritis. Funding: AbbVie Inc.